Co-optimization for fuel cell buses integrated with power system and air conditioning via multi-dimensional prediction of driving conditions. (1st November 2022) - Yan, Mei; Xu, Hongyang; Jin, Lisheng; He, Hongwen; Li, Menglin; Liu, Haoran
Graphical abstract: Highlights: A multi-dimensional future driving condition prediction for buses is proposed. Co-optimization for FCBs integrated with the AC system is proposed. The optimization balances energy economy and temperature comfort. The temperature comfort during operation is fully considered. Abstract: The unknown future driving conditions of actual fuel cell buses (FCBs) and the complex coupling between energy-consuming components make the energy management of integrated powertrain and electrical accessory systems challenging. To dress this challenge, based on the multi-dimensional prediction of driving conditions, a co-optimization integrated with power system and air conditioning system is proposed for fuel cell buses in this paper. The multi-dimensional accurate construction of future driving conditions is carried out from three perspectives: long-term velocity dynamic construction, passenger number prediction, and short-term velocity real-time prediction. On this basis, hierarchical and integrated optimization strategies are designed. The optimization objective function aims at energy consumption economy and rides comfort, incorporating the impact of fuel cell and battery degradation. The simulation experiment of co-optimization for FCBs integrated power system and air conditioning system is carried out. The simulation results show that compared to the hierarchical strategy, the integrated approach has better temperature comfort and energy-saving effect, where the average temperature is closest to the target comfort temperature of 25.55 °C, and the RMSE is 0.64 °C. The equivalent hydrogen consumption is relatively saved by 6.24 %, 7678.3 g/100 km, reaching 90.27 % of the benchmark solved by offline dynamic programming.